The Challenge of Implementing Pancasila Values to the Milenial Generation - Luthfianeza, Zulva Alya (Journal of Creativity Student, 2018)
Pancasila has been established as the basis of the state on June 1, 1945, growing as the ideology of the nation since the beginning of Indonesian independence as well as the unifying foundation of the nation. It contains divine values, humanity, unity and democracy that build social welfare. Right now we are starting to enter the millennial era where the generation of Y (aged 18-36 years) as a productive age is a milestone in determining the future of the Indonesian nation and how the whole Pancasila will be practiced as the basis of the nation. The whole world has been filled with rapid developments ranging from communication to industry. Globalization is both an advantage and a challenge for us, millennial generation. In this instant world era, we are faced with the challenge of how to synchronize the Pancasila culture and the strength of globalization that enters Indonesia, as we know some outside ideologies and cultures can be said to be out of line with ideology and culture in Indonesia itself. Opening up to change is not wrong, but it is needed for domestic development, but surely not all of these cultures can be practiced in life in Indonesia. We also have to filter out, choose the good to use / preserve, and the bad to be abandoned. In order for the millennial generation to still have the Pancasila foundation, then an understanding of the ideology of the Pancasila is needed, this can be obtained through formal, informal, and everyday life education. Developing attitudes that reflect the values of the Pancasila, such as being more critical in receiving information and disseminating it, moreover at this time the ITE Law is increasingly being emphasized to quell false news spread in online media. So in addition to technological advancements and the strong currents of globalization, as millennial generations that will determine the future of the nation, we must be able to balance the ideology of the Pancasila with the changing times where everything starts from ourselves and spread to the people around us. Let's be a millennial generation that has the character of an Indonesian Nation with the ideology of Pancasila.